A.P. bio. Season one. [videorecording (DVD)] - Rodriguez, Osmany; Howerton, Glenn, 1976-; Oswalt, Patton, 1969-; McCarthy, Jacob (Universal Picture Home Entertainment, 2018)
When disgraced Harvard philosophy scholar Jack Griffin (Glenn Howerton) loses out on his dream job, he is forced to return to Toledo, Ohio, and work as a high school Advanced Placement Biology teacher. As he comes crashing into Whitlock High School, Jack makes it absolutely clear he will not be teaching any biology. Realizing he has a room full of honor roll students at his disposal, Jack decides instead to use the kids for his own benefit. Eager to prove that he is still king of the castle, Principal Durbin (Patton Oswalt) struggles to control the force of nature that is Jack Griffin.